2018
DOI: 10.1002/ccr3.1845
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter aortic valve implantation in an orthotopic heart transplant recipient with bicuspid aortic valve

Abstract: Key Clinical MessageIncreasing longevity of heart transplantation recipients and aging donor population accompanied by the older age at transplantation led to an increase in the prevalence of degenerative valvular disease in particular aortic stenosis. TAVI is considered a safe and feasible alternative compared to conventional SAVR in this high‐risk population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 18 publications
(12 reference statements)
0
15
0
Order By: Relevance
“…[ 31 , 38 ] Bicuspid aortic valve is the most common congenital valvular abnormality in which only two cusps of the aortic valve are present since the separation of valve cusps does not happen in the fetal period. [ 7 , 31 ] Not only can this condition be defined at any age without any clinical findings but it also has a potential to cause stenosis and regurgitation in the aortic valve. [ 39 ] Although the appropriate treatment for transplant patients with bicuspid aortic valve is not clearly identified, this review found two different approaches in two different patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 31 , 38 ] Bicuspid aortic valve is the most common congenital valvular abnormality in which only two cusps of the aortic valve are present since the separation of valve cusps does not happen in the fetal period. [ 7 , 31 ] Not only can this condition be defined at any age without any clinical findings but it also has a potential to cause stenosis and regurgitation in the aortic valve. [ 39 ] Although the appropriate treatment for transplant patients with bicuspid aortic valve is not clearly identified, this review found two different approaches in two different patients.…”
Section: Discussionmentioning
confidence: 99%
“…While the first patient with bicuspid aortic valve received aortic valve replacement, the second patient underwent transcatheter aortic valve implantation (TAVI). [ 31 , 38 ] Additionally, there is limited data on the outcomes of TAVI in patients having bicuspid aortic valve; thus, there is no standard treatment that has been established for this condition and its associated valve dysfunction. [ 38 ]…”
Section: Discussionmentioning
confidence: 99%
“…Current adult transplant guidelines recommend consideration of donor hearts with functionally normal bicuspid aortic valves with a Class I recommendation 17 . Most of the adult transplant literature reporting the usage of donor hearts with bicuspid aortic valves comes from single case reports describing “bench” aortic valve replacement at time of transplant or catheter‐based valve replacement after valve failure 8‐16 . Peri‐transplant aortic valve replacement is appealing in adults due to the excellent exposure afforded to the surgeon.…”
Section: Discussionmentioning
confidence: 99%
“…17 Most of the adult transplant literature reporting the usage of donor hearts with bicuspid aortic valves comes from single case reports describing "bench" aortic valve replacement at time of transplant or catheter-based valve replacement after valve failure. [8][9][10][11][12][13][14][15][16] Peri-transplant aortic valve replacement is appealing in adults due to the excellent exposure afforded to the surgeon. In the pediatric population, it is a much less attractive choice due to the limited options for aortic valve prostheses in smaller patients, as well as concerns over the longevity of aortic valve replacements considering the increasing survival of pediatric heart transplant recipients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation